Analysis of K-Means Algorithm for Clustering of Covid-19 Social Assistance Recipients - Sri Rahmayani; S Sumarno; Zulia Almaida Siregar (JOMLAI: Journal of Machine Learning and Artificial Intelligence, 2022)
During the Covid-19 pandemic, the government provided assistance distributed through each sub-district throughout the province of Indonesia, one of which was the Pahlawan Village in the East Siantar District Pematangsiantar City. So far, the assistance provided by Kelurahan Pahlawan is still done manually, so errors in data collection and distribution of aid may occur. To overcome this problem, a study was carried out by applying the K-Means algorithm to determine the eligibility cluster of Covid-19 beneficiaries, which was carried out by collecting population data according to predetermined attributes. Then the population data will be clustered using the K-Means algorithm and tested using the Rapid Miner application. The clustering results obtained are that cluster 0 consists of 26 data and that cluster 1 consists of 24 data. The recipients of Covid-19 social assistance using the K-Means algorithm show that those entitled to receive the gift are the elderly (elderly). Based on this, it can be concluded that the K-Means Algorithm can be applied to produce more practical information in determining who is entitled to receive assistance